The effect of Chlorella vulgaris salep extract on the formation of bone remodeling - Herawati Hasan; Edy Machmud; Putri Alpiyanti (Makassar Dental Journal PDGI Makassar, 2020)
Background: Microalgae is a micro-plant that belongs to the algae class, its diameter is 3-30 µm, both single cells and colonies live throughout the water and sea commonly known as phytoplankton. Chlorella vulgaris is a species with low lipid levels but high cell growth, so it is interesting to study. Fast and easy growth and easy breeding make these microalgae profitable for use in the food, water culture, cosmetics, pharmacy industries, materials for treating waste water and biofuel production. Purpose: This article is aimed to find out the formulation of the extract of ointment C.vulgaris and the effect of the extract of C.vulgaris ointment on oral mucosa. Method: Experimental laboratory Conclusion: It can be concluded that the ointment preparation with a concentration of 5% is better than the concentration of 10% and 15%; ointment preparations do not cause irritation to the oral mucosa.